Efficient PEG-mediated transformation of oil palm mesophyll protoplasts and its application in functional analysis of oil palm promoters - Fizree, MD Piji Mohd Al Akmarul; Abdul Masani, Mat Yunus; Shaharuddin, Noor Azmi; Chai-Ling, Ho; Abd Manaf, Mohamad Arif; Parveez, Ghulam Kadir Ahmad (Elsevier, 2023)
The protoplast system is robust and versatile for plant genetic engineering works. There are various ways to deliver nucleic acid materials into the protoplasts, but polyethylene glycol (PEG)-mediated method offers minimal damage compared to others. Therefore, an established PEG-mediated transformation protocol with optimised parameters is needed to improve the systems reproducibility and reliability. This study utilised oil palm mesophyll protoplasts as transformation cells and the red fluorescent protein (DsRED) as a visual reporter. Based on the transformation efficiency scored after 72 h, a method with the following parameters: 5 min incubation in 35 PEG, 10 min incubation with 50 mg DNA, and 90 s heat-shock treatment at 42 °C was found to be the best for oil palm protoplast PEG-mediated transfection. A significant improvement in transformation efficiency at about 56 was achieved using this method compared to the previous study (5). This newly developed protocol was then used to evaluate the efficiency in terms of the relative strength of 7 promoters, including two plant constitutive promoters, three oil palm constitutive promoters, and two oil palm tissue-specific promoters in regulating the expression of the transgene in oil palm. Based on the results from three individual replicates, CaMV35S was shown to be the most efficient among the tested promoters in driving the transgene expression in oil palm mesophyll protoplasts, followed by oil palm translationally control tumour protein (TCTP) and maize-ubiquitin (Ubi1) promoters.